The impact of a primary care e-communication intervention on the participation of chronic disease patients who had not reached guideline suggested treatment goals. Issue 4 (April 2016) - Lussier, Marie-Thérèse; Richard, Claude; Glaser, Emma; Roberge, Denis
Highlights: Web-based educational approaches can improve patient participation in PC encounters. Trained groups engaged in more socio-emotional talk and more PACE utterances. Rate, initiative and dialogue on some medication themes increased in trained groups. Changes in patient participation were not perceived by patients themselves or their providers. Web based interventions are an accessible and effective way to activate patients. Abstract: Objective: To evaluate the efficacy of two web-based educational approaches on doctor-patient communication. The study focused on chronic disease (CD) patients in a lengthy relationship with their family physician (FP) who had not reached guideline suggested treatment goals (off-target) for their CDs. Methods: 322 hypertensive, diabetic, or dyslipidemic patients of 18 FPs were randomised into three groups: Usual Care (UC), e-Learning (e-L) and e-Learning + Workshop (e-L + W). Interventions were based on Cegala's PACE system: Prepare, Ask questions, Check understanding, Express concerns. Communication was evaluated using the Roter Interaction Analysis System (RIAS), MEDICODE and questionnaires. Results: Encounter length was similar across groups. RIAS showed that e-L + W group engaged in more socio-emotional talk and PACE-like utterances. MEDICODE showed that interventions increased frequency, initiative and dialogue for selected CD medication themes. Quality of communication was perceived as satisfactory at baseline and did not change. Conclusion: Following interventions, CD patients were more activated even in well-established doctor-patient relationships. Practice implications: PACE web-based interventions are accessible and effective at increasing CD patients' participation. They increase legitimacy to express the patient experience. FPs should present this type of training to CD patients as an integral part of their routine practice and consider referring patients to complete it.